1992
DOI: 10.3109/00365529208999956
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dehydrocholic and Cholic Acids on the Biliary Secretion of Anionic Polypeptide Fraction, the Major Apoprotein of the Biliary Lipoprotein Complex

Abstract: This work was undertaken to study the effect of intravenously infused dehydrocholate (DHCA) and cholate (CA) on lipid and anionic polypeptide fraction (APF) secretion in bile. APF is a small acidic amphipathic apoprotein closely associated with biliary lipids and bilirubin and involved in the control of bile-destined cholesterol. Rats were infused with increasing doses of DHCA (2 and 3 mumols/min/100 g b.w.) and then CA (1, 2, and 3 mumols/min/100 g b.w.). Each dose was infused for 30 min. As expected, intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The much more effective dose of 6% PC results in a significant increase in bile salts (such an increase could be associated with the ability to induce the micellar phase, as described elsewhere) (49) and a significant decrease in the CSI, suggesting a regulatory effect of the CSI in the effect of this level of PC supplementation. The decrease in APF level was shown previously in rats infused with cholic acid (50). Thus, we speculate that increasing the micellar phase may act by lowering the APF level and vesicular phase.…”
Section: Downloaded Frommentioning
confidence: 54%
“…The much more effective dose of 6% PC results in a significant increase in bile salts (such an increase could be associated with the ability to induce the micellar phase, as described elsewhere) (49) and a significant decrease in the CSI, suggesting a regulatory effect of the CSI in the effect of this level of PC supplementation. The decrease in APF level was shown previously in rats infused with cholic acid (50). Thus, we speculate that increasing the micellar phase may act by lowering the APF level and vesicular phase.…”
Section: Downloaded Frommentioning
confidence: 54%
“…However, in this study, the level of TUDCA was found to be elevated in NASH mice. Chanussot et al (1992) found that DHCA can inhibit the secretion of phospholipids and cholesterol to achieve the effect of protecting the liver. Similar results were found in the present study.…”
Section: Kaempferol Improves Nash By Regulating the Homeostasis Of Ba...mentioning
confidence: 99%
“…It is the third most abundant protein in human bile after albumin and IgA (3). Unlike these two proteins, the biliary secretion of APF in rats is modulated by bile salts (4 APF is secreted by isolated hepatocytes, and its secretion is enhanced by bile salts (2). The potential physiological and pathophysiological properties of this biliary protein are only beginning to be explored.…”
Section: Tuvia Gilat~mentioning
confidence: 99%